Expression profiles of long and short RNA s in the cytoplasm and nuclei of growing chicken (Gallus gallus domesticus) oocytes - A. V. Krasikova; A. V. Fedorov (Вавиловский журнал генетики и селекции)
Maternal RNAs accumulated during oocyte maturation are required not only for zygote formation but also for supporting the first embryonic cell divisions until embryo genome activation. Essential stages of transcriptome analysis include adaptation of RNA extraction procedures and characterization of the RNA expression profile. Ovaries of domestic birds represent an adequate model for exploration of RNA accumulation during oogenesis. In the present study, we optimized methods of RNA extraction from chicken (Gallus gallus domesticus) oocyte cytoplasm and nucleoplasm and characterized changes in profiles of long and short RNAs during oocyte growth. Cytoplasmic RNA fractions contained 28S and 18S ribosomal RNAs (rRNAs), small RNAs, and long RNAs heterogeneous in size. The profiles of total RNA from growing oocyte nuclei were dominated by low molecular weight RNAs corresponding in size to transport RNAs, small nuclear RNAs, and short regulatory RNAs. Importantly, oocyte nuclei from chicken egglaying females demonstrated trace amounts or absence of 28S and 18S rRNA, which was due to inactivation of the only nucleolar organizer. Three groups of short RNAs differing in size (from 20 to 40 nucleotides) were recognized in chicken oocytes. They might correspond to short regulatory RNA classes. Furthermore, we demonstrated that short RNAs were accumulated in the cytoplasm during oocyte growth. We suggest that short RNAs accumulated in avian oocyte cytoplasm are involved in the regulation of genome functions at early embryogenesis stages.